THE 'MODEL STATE' MODEL: Southern Mato Grosso and the post 1964 coup demands submitted to it - Buscioli, Roberson da Rocha [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2020)
In this article we seek to understand the institutionalization of planning within the State after the 1964 coup, and definition of regional integration policy as a measure of development for the Southern Mato Grosso, having as object of analysis a set of development plans and programmes directed towards this space in the years of the Military Dictatorship. The following research procedures have been adopted: revision of the literature, first by seeking to understand the system of (re)production of capital, its relationship with the State and space ( re)production, thus, exploring the ideological discourse which gives it supports. Secondly by seeking government official documents institutionally responsible for planning, implementing and monitoring public planning and development policies to better understand the policies adopted in the period, as well as the production of charts, graphs and cartographic products. As a result of this, we have noted the work of the State in adjusting that space for further reproduction of capital which has culminated in its constitution as a Federal Unit, discursively presented as strategic for development in the region, guided by the adoption of a biased development strategy, configuring itself in the elevation of some cities to the development pole status, with a high concentration of resources in implementing logistics infrastructure, agricultural storage and research, and expansion of financing lines for agribusiness, confirming the State`s role as an essencial public fund for capitalistic development.
Keywords: Public Policies; Spatio-temporal adjustment; Southern Mato Grosso; division of space in Mato Grosso do Sul